Investigation and prevention of financial crime knowledge management, intelligence strategy and executive leadership - Gottschalk, Petter 1950- author (Routledge, 2016)
So long as there are weaknesses that can be exploited for gain, companies, other organizations and private individuals will be taken advantage of. This theoretically-based but hugely practical book focuses on what is generally seen as financial or economic crime: theft, fraud, manipulation, and corruption. Petter Gottschalk considers how, in some competitive environments, goals can 'legitimise' all kinds of means, and how culture can exert a role in relation to what is seen as acceptable or unacceptable behaviour by individuals. In Investigation and Prevention of Financial Crime he addresses important topics including organized crime, money laundering, cyber crime, corruption in law enforcement agencies, and whistleblowing, and provides expert advice about strategies for the use of intelligence to combat financial crime.